Case report: Coxiella burnetii endocarditis in the absence of evident exposure - Bozza, Silvia; Graziani, Alessandro; Borghi, Monica; Marini, Daniele; Duranti, Michele; Camilloni, Barbara (Frontiers in Medicine, 2023)
Q fever is a worldwide zoonotic disease caused by Coxiella burnetii. In humans, it can manifest clinically as an acute or chronic disease and endocarditis, the most frequent complication of chronic Q fever, is associated with the greatest morbidity and mortality. We report a severe case of endocarditis in a 55-year-old man with a history of aortic valve replacement, affected by monoclonal gammopathy of undetermined significance (MGUS), and living in a non-endemic area for C. burnetii. After two fever of unknown origin (FUO) episodes, occurring 2 years apart and characterized by negative blood cultures, a serological diagnosis of Q fever endocarditis was performed, even though the patient didn’t refer about a possible past exposure to C. burnetii. Since people with preexisting valvular heart disease, when infected with C. burnetii, have a reported 40% risk of Q fever endocarditis, clinicians should maintain a high index of suspicion for infective endocarditis in all patients with FUO, even when the exposure to C. burnetii appears to be unlikely.